QUALITY ASSURANCE OF MAQASID SYARIAH-BASED ISLAMIC COLLEGES - Zuraidah, Zuraidah; Aisyah, Esy Nur (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
In improving the quality assurance in Islamic colleges, internal and external harmony, conformity with standards, conformity of expectations, suitability of objectives, suitable of use and others that are in accordance with higher education are very important. This study uses qualitative method approach verification through the measurement of Quality Assurance of Educational Service in Islamic Colleges, such as: 1) Tangible, 2) Reliability, 3) Responsiveness, 4) Assurance and 5) Empathy that are combined with Key Success Factors of Educational Service Quality and analyzed by Maqasid Sharia. The result is Maqasid Sharia is an indicator in harmonizing the result of quality assurance measurement of educational service and Key Success Factor of Educational Service in Islamic Colleges. The aim of Maqasid Sharia existence is to realize the benefit of goodness for human beings in this world and in the hereafter.This study can also be used as a reference as an effort to become a Muslim who is professional and intellectual in carrying out his obligations and also has a sense of responsibility that must be carried out. Because Islam teaches its followers to responsible for what are done.